2016
DOI: 10.1186/s13058-016-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

Beyond breast density: a review on the advancing role of parenchymal texture analysis in breast cancer risk assessment

Abstract: BackgroundThe assessment of a woman’s risk for developing breast cancer has become increasingly important for establishing personalized screening recommendations and forming preventive strategies. Studies have consistently shown a strong relationship between breast cancer risk and mammographic parenchymal patterns, typically assessed by percent mammographic density. This paper will review the advancing role of mammographic texture analysis as a potential novel approach to characterize the breast parenchymal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 108 publications
(134 reference statements)
8
123
1
2
Order By: Relevance
“…34 Manual feature engineering is about crafting well-defined features (such as shape, contour, texture) to directly describe domain knowledge, such as imaging appearance characteristics. 35,36 Researchers have crafted hundreds of computer features 9,35,37 and tested them in many applications in a trial-and-error manner to identify those that work best for specific tasks. 38 However, it is not always straightforward to translate qualitative and tactic radiological domain knowledge to exact mathematic descriptors to support manual feature engineering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Manual feature engineering is about crafting well-defined features (such as shape, contour, texture) to directly describe domain knowledge, such as imaging appearance characteristics. 35,36 Researchers have crafted hundreds of computer features 9,35,37 and tested them in many applications in a trial-and-error manner to identify those that work best for specific tasks. 38 However, it is not always straightforward to translate qualitative and tactic radiological domain knowledge to exact mathematic descriptors to support manual feature engineering.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In addition to breast density, studies have shown that the mammographic imaging texture features of breast tissue are also related to breast cancer risk. 9,10 Texture descriptors such as energy, contrast, correlation, etc. compute the local properties at each pixel and derive a set of statistics information from the local properties' distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to generating reproducible, quantitative metrics, these methods allow estimation of a continuous score, rather than a categorical assessment, which may allow for more granular density-based risk stratification for women. subjective assignment of BI-RADS density categories by providing reproducible estimates of both the risk of masking a cancer as well as the risk of developing breast cancer-two important factors in determining personalized breast cancer screening algorithms (35).…”
Section: Opinion: Beyond Bi-rads Densitymentioning
confidence: 99%
“…Women with an extensive degree of breast density have a two to sixfold higher risk of breast cancer compared to women with little density . Although there are several established methods to analyze mammograms for risk purposes, to date there is not a recognized standard for breast density determination clinically . To address this situation, our ongoing breast density work includes developing calibrated metrics based on imaging reference phantoms.…”
Section: Introductionmentioning
confidence: 99%